THE CODE - MIXING AND CODE - SWITCHING IN TEACHING ENGLISH AT SEVENTH GRADE OF SMP N 1 RAYA - Semaria Eva Girsang; Novi Iramasniari Saragih (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2021)
The objective of this research was to find types of code-mixing and code-switching used in teaching English Raya and to find the factors of using code-mixing and code-switching in teaching English. This research was conducted at SMP N 1 Raya with method of this research used qualitative content analysis method. Population and sample of this research was all of English teachers’ statement which contain code-mixing and code-switching in teaching English at seventh grade of SMP N 1 Raya. The technique of collecting data was recording and interview. The result of this research showed that there were 31 utterances three types of code-mixing and 56 utterances types of code-switching that used by English teachers in teaching learning process. Code-mixing namely intra-sentential code-mixing, intra-lexical code-mixing and involving change of pronunciation. Intra-sentential code mixing was the dominant type that used by English teachers in teaching learning process, which is 24 utterances included intra-sentential code-mixing, 3 utterances included intra-lexical and 4 utterances included Involving change of pronunciation. Code-switching namely tag code-switching, inter-sentential code-switching and intra-sentential code-switching. Inter-sentential code-switching was the dominant type that used by English teachers in teaching learning process, which is 52 utterances included inter-sentential code-switching and 4 utterances included tag code-switching.While the factors of English teachers used code mixing in teaching learning process were social factor whereas topic, participant and situation become aspects which influenced they mixed and switched their language